A cross-cultural perspective of voluntary disclosure: Italian listed firms in the stakeholder global context. (2017) - Coluccia, Daniela; D'Amico, Eugenio; Fontana, Stefano; Solimene, Silvia
Through this paper, we empirically studied the presence, evolution, and determinants of voluntary disclosure with reference to the Italian Stock Exchange context in a multi-stakeholder approach. In particular, we identified eight stakeholders: customers, suppliers, competitors, institutions, community, environment, human capital and corporate governance, and financial lenders. For each one, we verified its disclosure in the following years: 2006, 2009, and 2012. As far as the presence and evolution of disclosure, our results show that there has been indeed an increase of disclosure, especially during the period 2009-2012. But it is still far from the level required by international organisations (Guidelines of the Global Reporting Initiative; Guidelines for ESG approved by the European Federation of Financial Analysts Societies; Guidelines developed as part of the CSR-SC project, prepared by the Italian Ministry of Labour and Social Policy). With reference to the determinants, we applied a mixed logit model for generalised binomial random variables that allowed us to see that the only variable that positively affects the disclosure of each stakeholder is the firm size.